ANALISIS PERSEDIAAN DAN KESEIMBANGAN INVENTORY: STUDI PADA RESTORAN KAWAII SUSHI YOGYAKARTA - , Silvia Utami Siregar ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research is originated from the multiple problems faced by Kawaii Sushi Restaurant of Yogyakarta in managing their inventories starting from the optimum quantity of raw material purchases, the high ordering cost until the frequent occurrence of order delivery delay to customers. Object researched is the bestseller sushi menu with demands over 100 servings every month and also its raw materials. The analysis the optimum quantity of the raw material at this research done based on MRP models for restaurant services and then continued with the calculations using the Economic Order Quantity models and reorder point. Further, the analysis of the Fix Order Interval model used to minimize ordering cost. On the other hand, delivery delay analysis performed by using the service level calculation. Finally, the calculation of the inventory balance carried to balance the inventory investments and service levels to the consumers. The results of identification state that Kawaii Sushi doesnât use certain inventory models (according to theory) to manage the entire inventory. Meanwhile, the FIFO (first in first out) system is used to manage the storage of the raw materials. Whereas, delivery delays that occur tend to be caused by the employee's performance, not because of the shortages of stock. The results of the Economic Order Quantity analysis show that Tobiko has the highest annual total cost and Salt is the lowest one. Desire of management to reach 99% service level will increase the reorder point from the the amount of reorder point without safety stock. No one of all the sushi menus with the highest demand has reached 99% service level. The highest service level is attained by Tobiko Gunkan menu (89,8%) and the lowest one is owned by California Roll menu (71,4%). The highest inventory balance is achieved by Tobiko Gunkan menu (2,64 servings) while the lowest point is obtained by Grill Salmon Roll menu (1,79 servings).